Immunoregulatory effects of sizofiran (SPG) on lymphocytes and polymorphonuclear leukocytes. - Yoneda, K (1991)
The effect of SPG on leukocytes has been studied in 20 patients with oral carcinoma and the actions have been analysed in vitro. SPG 1 mg/kg was administered intramuscularly twice weekly. Peripheral venous blood was collected before, and 1 week and 2 weeks after the initiation of SPG treatment. Both CD16+CD57- and CD16-CD57+ cell populations were significantly increased after treatment, but no T cell subset varied. While enhancement of lymphokine-activated killer activity could not be found, an increase in natural killer (NK) activity was observed in 15 of the subjects, and the mean NK level was significantly increased from an initial 34.7 +/- 18.7% to 46.4 +/- 16.5% after two weeks of injections. O2-production by polymorphonuclear leukocytes (PMNL) was stimulated 6 h after SPG injection. When PMNL were treated in vitro with SPG 32 micrograms/ml, enhanced O2-generation was induced and protein kinase C (PKC) activity in a membrane fraction increased. SPG did not directly affect non-specific PMNL killing of K562 cells or antibody-dependent cell mediated cytotoxicity against Raji cells, but non-specific PMNL killing was enhanced by culture-conditioned medium from peripheral blood mononuclear cells (PBMC) containing 10 micrograms/ml SPG. Interleukin-1 beta, -3, -4, -6, tumour necrosis factor-alpha, granulocyte-macrophage colony stimulating factor and IFN-gamma levels in the conditioned medium were not increased compared with medium from PBMC not treated with SPG. No clear increase of these cytokines was found in serum from the SPG-treated patients. From the above results, enhancement of PMNL O2-generation by SPG seems to be a direct action of SPG, but the mechanism of elevation of the non-specific killing activity of PMNL and NK cells is not known. Perhaps other cytokines than those assayed have participated in increasing non-specific cytotoxicity.